The Urgency of Legal Protection of Digital Work Copyright - Rio Putra Simanjuntak; Lamijan Lamijan; Wieke Dewi Suryandari (Pusat Publikasi Nusantara, 2024)
With the development of the times, science and technology are developing very quickly, allowing traditional works which are usually in physical form to be transformed into digital format. This research aims to examine legal protection methods for intellectual works in a digital context and identify the role of the government in preventing piracy of digital works. This research uses a normative juridical approach, which views law from the perspective of texts in statutory regulations and norms or standards of behavior that are considered appropriate. Copyright Law Number 28 of 2014 Article 4 articulates that copyright is an exclusive right that includes moral rights and economic rights. Individuals who wish to use the Economic Rights of a work must obtain permission from the creator or copyright owner. The legal protection is confirmed by a firm and appropriate sanctions by law enforcers by existing legislation.